2014
DOI: 10.4103/1357-6283.134313
|View full text |Cite
|
Sign up to set email alerts
|

A study of obstetricians′ knowledge, attitudes and practices in oral health and pregnancy

Abstract: This study found that although obstetricians generally were knowledgeable about appropriate dental care practices during pregnancy as well as the relationship between oral health and pregnancy outcomes, this knowledge often did not translate into appropriate practice behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
2
15
1
1
Order By: Relevance
“…Surveys conducted in other regions of the world have shown that visits to the dentist during pregnancy are suggested by 44% to 93.9% of specialists [28][29][30][31][32]. A relation between the referral of pregnant women to the dentist and knowledge about the impact of oral health on pregnancy has been shown [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys conducted in other regions of the world have shown that visits to the dentist during pregnancy are suggested by 44% to 93.9% of specialists [28][29][30][31][32]. A relation between the referral of pregnant women to the dentist and knowledge about the impact of oral health on pregnancy has been shown [31].…”
Section: Discussionmentioning
confidence: 99%
“…A relation between the referral of pregnant women to the dentist and knowledge about the impact of oral health on pregnancy has been shown [31]. According to Reddy et al, gynaecologists have the knowledge and proper approach to preventing oral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, obstetricians appear more supportive of medications during pregnancy as opposed to alternative medicines for pain. For example, a survey of obstetricians found that 80% felt paracetamol was appropriate to recommend during pregnancy for dental pain [38]. Better use of social media such as Facebook and Twitter may have been useful for increasing recruitment rates.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially important to have a dental check-up, dental cleaning, and any necessary treatment during pregnancy. Delaying necessary treatment for oral health problems during pregnancy could result in significant risk to a mother and baby [6] [7]. The second trimester is a good time to schedule a routine visit to a dental professional, however, if a pregnant woman experiences a problem at any time during pregnancy, she is advised to seek professional help immediately [8].…”
Section: Introductionmentioning
confidence: 99%